Cropguard and pest control system - Mandeya, Shamiso (Midlands State University, 2019)
This project was focused at designing and implementing an android cropguard and pest control application system which will assist farmers to acquire farming knowledge and know how they can deal with pests and diseases so as to improve the output. Experts in farming will be able to offer expert advice to farmers and as well acquire additional knowledge and try new crops. Farmers would be able to report their needs to the ministry of agriculture and make the ministry of agriculture recognize farmers in different regions. Ministry of Agriculture Information Technology will be able to assign roles to the experts and extension officers and create a knowledge base which will be useful in the future. Experts remains in their line of expertise thereby could not try different crops. They remain with limited information but through the use of the proposed system they will be able to increase their knowledge. Administrators spends a lot of time in offices but due to the use of the system they will be able to try farming during weekends and public holidays which intern benefit them and their families. Farmers has no knowledge of where exactly they ca access farming products and their prices. Farm shops has no knowledge of which products should always be available in storage